2006
DOI: 10.1126/science.1120182
|View full text |Cite
|
Sign up to set email alerts
|

Fuel-Powered Artificial Muscles

Abstract: Artificial muscles and electric motors found in autonomous robots and prosthetic limbs are typically battery-powered, which severely restricts the duration of their performance and can necessitate long inactivity during battery recharge. To help solve these problems, we demonstrated two types of artificial muscles that convert the chemical energy of high-energy-density fuels to mechanical energy. The first type stores electrical charge and uses changes in stored charge for mechanical actuation. In contrast wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(74 citation statements)
references
References 19 publications
1
70
0
Order By: Relevance
“…Electrostatic attraction and repulsion between two nanotubes have been used for cantilever-based nano-tweezers 101 and mechanically based switches and logic elements. 102,103 On the macroscale, electrically powered [104][105][106][107][108][109][110][111] and fuel-powered 112,113 electrochemical carbon nanotube actuators provide up to a few percent actuator stroke and over a hundred times higher stress generation than natural muscle. Large-stroke pneumatic nanotube actuators have been demonstrated that use electrochemical gas generation within nanotube sheets.…”
Section: Carbon Nanotube-based Artificial Musclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrostatic attraction and repulsion between two nanotubes have been used for cantilever-based nano-tweezers 101 and mechanically based switches and logic elements. 102,103 On the macroscale, electrically powered [104][105][106][107][108][109][110][111] and fuel-powered 112,113 electrochemical carbon nanotube actuators provide up to a few percent actuator stroke and over a hundred times higher stress generation than natural muscle. Large-stroke pneumatic nanotube actuators have been demonstrated that use electrochemical gas generation within nanotube sheets.…”
Section: Carbon Nanotube-based Artificial Musclesmentioning
confidence: 99%
“…This time, the actuating carbon nanotube electrodes simultaneously function as fuel cell electrodes to convert chemical energy to electrical energy in the form of stored charge, as supercapacitor electrodes to store this charge, and as actuators that convert changes in stored charge to actuator stroke. 112,113 The exploitation of charge-injectionbased carbon nanotubes for highly reversible, high-cycle-life muscles requires the elimination of a major problemirreversible plastic deformation occurring under high load conditions, which increases the strain obtained at a provided electrode potential. The strain rate of this plastic deformation, which depends on electrode potential and the mechanical load on the muscle, has recently been substantially decreased through the use of solid-state fabricated twisted nanotube yarns containing ~300-μm long carbon nanotubes.…”
Section: Carbon Nanotube Muscles Based On Electrical or Chemical Doubmentioning
confidence: 99%
“…Light actuation is not always practical. A challenge for the synthetic chemistry and materials communities is to develop molecular mechanisms that are activated directly or indirectly by high energy fuels [e.g., hydrogen and oxygen (37)]. …”
Section: New Approachesmentioning
confidence: 99%
“…For example, the actuation of an IPMC micro-pump, powered by a small MFC, could be used to deliver the low flow rate of anolyte that is required by small MFCs [7]. diapraghm expansion to feed diapraghm depression to excrete diapraghm neutral Previous studies have combined energy generation with actuation in a single component of a fuel cell by the chemical gradients present in a fuel cell to drive gradual actuation, for example, [2] considers components dual functionality as electrodes and actuators for mixing in the anolyte chamber. Agitation of anolyte within the MFC has been shown to increase mass transfer of the anolyte to the biofilm, stimulating increased power production [4], hence by inclusion of an IPMC within the MFC bacterial environment this study evaluates the suitability of IPMCs for use in internal mixing of MFC anolyte ( Figure 6).…”
Section: Ipmc Actuationmentioning
confidence: 99%